Description of a new clinical syndrome: thoracic constriction without evidence of the typical funnel-shaped depression - the "invisible" pectus excavatum - Hohneck, Anna; Ansari, Uzair; Natale, Michèle; Wittig, Karsten; Overhoff, Daniel; Riffel, Philipp; Boettcher, Michael; Akın, Ibrahim; Dürschmied, Daniel; Papavassiliu, Theano (Scientific reports, 2023)
Pectus excavatum (PE) is a congenital malformation with a funnel-shaped depression of the sternum that can lead to cardiac symptoms. However, there are patients with thoracic constriction (defined as elevated Haller-Index > 3.25 determined by cardiac magnetic resonance imaging (CMR)) without visible evidence of PE, leading to similar complaints. Between January 2004 till June 2020, patients who underwent CMR for further evaluation of the heart, due to cardiac symptoms were enrolled and compared to controls. Biventricular global strain analysis was assessed using feature tracking (CMR-FT). ECG and/or Holter recordings were performed to detect rhythm events. Cardiac symptoms were evaluated in detail using a questionnaire. Finally, 88 patients (male 35, female 53) with elevated Haller-Index (3.9 ± 0.8) were included and compared to CMR data from 25 individuals with confirmed PE and 25 healthy controls (HC). Mean age at time of CMR was 35 ± 16 years. The most common symptoms at presentation were palpitations (41%), followed by dyspnea (24%) and atypical chest pain (14%). Three patients (3%) had atrial fibrillation or atrial flutter. Concomitant phenomena were pericardial effusion in 39% and mitral valve prolapse (MVP) in 27% of the study cohort. While there were no differences in left ventricular function or volumes, right ventricular function (RVEF) was significantly lower in patients with internal PE compared to HC (RVEF (%) 50 ± 5 vs 59 ± 4, p < 0.01). Strain analysis revealed only discrete changes in RV strain, implying a purely mechanical problem in the absence of structural changes. RV dimensions were negatively correlated with the size of thoracic indices (r = 0.41), reflecting the extent of thoracic constriction. MVP was more prevalent in patients with greater thoracic indices (r = 0.24). The described cohort, referred to as internal PE because of the absence of external changes, showed similar CMR morphologic findings as patients with real PE (especially altered dimensions of the right heart and a lower RVEF). In addition, there was a high incidence of rhythm disturbances, such as extrasystoles or arrhythmias. In one-third of the study cohort additional abnormalities such as pericardial effusion or MVP were present, with MVP being found more frequently in patients with larger thoracic indices, suggesting a possible common pathogenesis.